2021
DOI: 10.1055/a-1640-4365
|View full text |Cite
|
Sign up to set email alerts
|

The endoscopic ultrasound features of pancreatic fluid collections and their impact on therapeutic decisions: an interobserver agreement study

Abstract: Background and study aims: A validated classification of endoscopic ultrasound (EUS) morphological characteristics and consequent therapeutic intervention(s) in pancreatic and peripancreatic fluid collections (PFCs) is lacking. We performed an interobserver agreement study among expert endosonographers assessing EUS related PFCs features and therapeutic approaches utilized. Patients and methods: Fifty EUS videos of PFCs were independently reviewed by 12 experts and evaluated for PFC type, percentage of solid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The latter often infiltrates adjacent structures, has irregular contours, and is associated with pseudopods; hence, it is difficult to obtain an accurate measurement of the tumor diameter. Despite the fact that several interobserver agreement studies have been conducted with EUS for diagnosis of pancreatic diseases such as chronic pancreatitis and accumulation of pancreatic fluid, very few have included solid pancreatic masses, especially PDAC 8 9 10 11 12 13 14 . Moreover, only endosonographers have taken part in these pilot or multicenter studies, and no radiologists were included in the panel of experts.…”
Section: Methodsmentioning
confidence: 99%
“…The latter often infiltrates adjacent structures, has irregular contours, and is associated with pseudopods; hence, it is difficult to obtain an accurate measurement of the tumor diameter. Despite the fact that several interobserver agreement studies have been conducted with EUS for diagnosis of pancreatic diseases such as chronic pancreatitis and accumulation of pancreatic fluid, very few have included solid pancreatic masses, especially PDAC 8 9 10 11 12 13 14 . Moreover, only endosonographers have taken part in these pilot or multicenter studies, and no radiologists were included in the panel of experts.…”
Section: Methodsmentioning
confidence: 99%
“…The authors shared shortduration EUS videos of 50 patients with a PFC, without their clinical correlates, that were independently reviewed by 12 experts and evaluated for eight features: five diagnostic (type of collection, percentage solid debris, presence of infection, main pancreatic duct [MPD] recognition, and PFC-MPD communication) and three therapeutic (type of stent for drainage, and the requirement for DEN and its timing). The study reported poor interobserver agreement for all of the morphological features of PFCs examined (except for PFC-MPD communication), which is not unusual given the subjective nature of EUS evaluation, including crucially the assessment of debris [3]. Notably, even the landmark studies did not mention the methods for measurement of percentage debris [4,5].…”
mentioning
confidence: 92%
“…There were no available data from interobserver agreement studies on the morphological characterization of PFCs and the subsequent therapeutic decisions. The study by Fabbri et al address the knowledge gap on some of the parameters in this interobserver agreement study [3].…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Lumen-apposing metal stents (LAMSs) have revolutionized endoscopic treatment of walled-off necrosis (WON) by allowing for effective drainage and subsequent endoscopic necrosectomy [1,2]. However, it may be technically challenging to deploy a LAMS for a WON with little fluid content [3], which potentially inhibits insertion of the delivery and expansion of the distal stent flange [4]. A 38-year-old woman was referred to our department for endoscopic management of an infected WON due to biliary pancreatitis (▶ Fig.…”
mentioning
confidence: 99%